Status quo and influencing factors of comfort with touch among nursing staff in rehabilitation department: A cross-sectional study - Yun Jie TONG; Dan-Dan LU; Mei-Fen LYU; Yan-Mei LIU; Shi-Yun TAN (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of this study is to investigate the current status of comfort with touch among nursing staff in the rehabilitation department and analyze its influencing factors. Materials and Methods: The convenience sampling method was used to select 131 nursing staff in the rehabilitation department of 3A-level hospitals in Yunnan Province, China, from March to June 2020 to conduct a questionnaire survey. Results: The nurses' comfort with touch score of 131 clinical nurses in the rehabilitation department was 58.82 ± 4.85. Multivariate regression analysis showed that compassion fatigue (t = ‒2.968, P < 0.01) and occupational social support (t = 2.767, P < 0.01) were the influencing factors of the physical comfort of nursing staff; average monthly income (t = ‒2.160, P < 0.05), occupational cognitive evaluation (t = 4.924, P < 0.01), and secondary traumatic stress (t = 2.833, P < 0.01) were the influencing factors of task-oriented contact among nursing staff; marital status (t = 2.656, P < 0.01) and occupational social support (t = 2.078, P < 0.05) were the influencing factors for private nursing comfort of nurses. Conclusion: The comfort with touch among nurses in the rehabilitation department is at a medium level. Nursing managers should pay attention to their comfort with touch. In order to promote the development of medical service, hospitals should constantly improve the security and social support of nursing practitioners from the aspects of system, management, and salary performance.